An Updated Review For Hyperuricemia and Gout Management; Special Focus on the Available Drug Delivery Systems and Clinical Trials - Karantas, Ioannis D.; Miliotou, Androulla N.; Siafaka, Panoraia I. (Current Medicinal Chemistry, 2024)
Background: Hyperuricemia belongs to metabolic syndromes where increased uric acid levels are identified in the blood serum. Such a syndrome could be responsible for kidney stone formation, gout, hypertension, and chronic kidney diseases. It has been reported that cardiovascular risks have been linked with hyperuricemia. Gout is of the most frequent manifestations due to hyperuricemia; its management involves various pharmacological available options and dietary changes. Throughout the literature, various dosage forms are studied as alternative options to the present drug delivery systems. Objective: To update and summarize the current information for gout and hyperuricemia management. Methods: Authors have performed a thorough literature research from 2010-2023 using keywords such as hyperuricemia, gout, diagnosis, guidelines, drug delivery and clinical trials. The databases used were PubMed, ScienceDirect. According to our inclusion criteria, all studies which include the previous terms, as well as drugs or other molecules that can be applied for gout and/or hyperuricemia management, were added. Results: In this article, authors have summarized the pathogenesis, diagnosis and updated guidelines for gout and hyperuricemia management. Moreover, the authors have reviewed and discussed current drug delivery systems found in the literature, including drugs targeting the above disorders. Finally, the available clinical trials assessing the efficacy of newer drugs or combinations of the past ones, are being discussed. Conclusion: The available drugs and dosage forms are limited, and therefore, scientific society should focus on the development of more efficient drug delivery systems for hyperuricemia and gout management.
Keywords: gout